EPICARDIAL FAT: A STRIKER OR A SPARE? - O. M. Drapkina; O. N. Korneeva; Yu. S. Drapkina (Столичная издательская компания, 2015)
Epicardial fat is hormonally active tissue and has a direct impact on the myocardium state and coronary blood flow. The relationship of epicardial fat size and waist circumference with different clinical and metabolic parameters and coronary atherosclerosis severity in patients with ischemic heart disease is discussed.